Tuberculosis visualized with the ultrasound probe: a systematic review of sonographic pattern descriptions and an analysis of common sonographic features - Weber, Stefan F.; Manten, Katharina; Kleiber, Katharina; Ruby, Lisa; Grilli, Maurizio; Tobian, Frank; Bélard, Sabine Miriam; Denkinger, Claudia M. (Open Forum Infectious Diseases, 2025)
Evidence on tuberculosis (TB) ultrasound patterns is scarce. We systematically reviewed the literature aiming to identify common TB ultrasound features. Sources included PubMed, Cochrane Library, and others (1 January 2000 through 30 August 2021). Any article type (retrospective, prospective, cases, trials) with verbal ultrasound descriptions of TB were included; those with <2 ultrasound features were excluded. We adapted Murad et al (2018) for quality assessment. The outcome was a descriptive frequency ranking of ultrasound features and patterns (combinations) per organ. From 388 publications, 613 ultrasound descriptions across 23 organs from 2167 individuals (465 single cases, 1702 from case series/studies) were extracted. The most commonly described sonographic patterns related to the female breast (n = 45), the liver (n = 40), and the pancreas (n = 37). The synthesis reveals sonographic TB patterns, but is constrained by limited representativeness of studies and the partly subjective analysis. Our review may serve as a clinical or research resource.PROSPERO (CRD42021283319)